Dinâmica do fósforo em diferentes sistemas de manejo do solo - Cândido, Clebson Santos (2011)
The forms and availability of phosphorus vary with the soil characteristics and properties.The objective of this study was, by sequential extraction, changes in forms of P in the soil under no-tillage system under alley cropping with six years of implementation; tillage in alley cropping with three years of implementation; pasture area, area of soil with tillage, and an area of scrub. The P fractionation method developed by Hedley et al. (1982) was efficient to evaluate the effects of management changes in the dynamics of the forms of P in the soil. Results showed that in the alley cropping system were predominant forms of inorganic labile and moderately of P. Higher fractions of organic phosphorus (Po) were found in the system of cultivation under pasture.